Interpretation of Social and Natural Reality in Western and Eastern Philosophy - E. K. Bulyga; E. S. Logovaya (Наука и техника)
Taking Eastern and Western cultural and philosophical traditions as an example the paper analyzes historical- and philosophical and historical- and typological notion of «social and natural reality». Evident tendencies of world globalization pose a problem to work out a strategy for the whole civilization. This strategy should involve in itself all the best that have been created by Eastern and Western cultures.